ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI PERTUMBUHAN ASET BANK SYARIAH DI INDONESIA TAHUN 2009 -2019 - Labib Faruqi (Univ Ibn Khaldun Bogor, 2020)
The bank has a role in collecting public funds because it is an institution that is trusted by the public of various kinds to place in relation safely. Islamic banks in Indonesia increase significantly each year, but the growth rate of Islamic banks continues to increase. Then it is necessary to analyze the growth of assets in Islamic banking in Indonesia. This study analyzes the factors that influence the growth of Islamic bank assets in Indonesia. The factors examined were divided into 2 namely internal factors and external factors. Internal factors consist of results for CAR, NPF, DPK, and JKB, while external factors consist of inflation and the BI Rate. The processed data source is the monthly statistics of sharia banking from January 2009 to July 2019, and the method of analysis of this study uses VAR / VECM. The results showed that internal factors determine the growth of assets, increase in Revenue Sharing, JKB and DPK are very decisive factors, external factors are not significant to the growth of Islamic bank assets. And there is no causality between internal factors and external factors.